In vitro study of bioactive glass coatings obtainedby atmospheric plasma spraying - Cañas, Eugeni; Grünewald, Alina; Detsch, Rainer; Orts, María José; Sánchez, Enrique; Boccaccini, Aldo R. (Boletin De La Sociedad Espanola De Ceramica Y Vidrio, 2020)
This research has addressed a complete study of the bioactivity of bioactive glass coatingsobtained by atmospheric plasma spraying. The coatings have been characterized in termsof microstructure, adhesion, crystalline phases and bioactivity. Hydroxycarbonate apatiteformation was also monitored following a standard protocol and the in vitro cell responsewas evaluated by human osteoblast-like cells (MG-63 cells) incubation.The obtained coatings shown a microstructure typical of glass coatings. A simulated bodyfluid test proved that coatings are capable of developing a surface layer of hydroxycarbon-ate apatite whereas the appearance of this phase takes place at a longer time than thatobserved for the powder feedstock. Cell-culture test showed multidirectional growth of MG-63 cells which promoted good contact between cells and the surface of the coating. Thisstudy has confirmed a positive effect of the coatings in terms of surface bioactivity and, moreinterestingly, it has proven an adequate cell-material interaction on the coating surface.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Atmospheric plasma spraying; Bioactive glass coatings; Bioactive glass powder; Cell culture test; Simulated body fluid